Remote sensing of glaciers in the tropical Andes: a review. Issue 23 (2nd December 2017) - Veettil, Bijeesh K.; Kamp, Ulrich
ABSTRACT: While the tropical Andes of Venezuela, Colombia, Ecuador, Peru, Bolivia, northern Chile, and northern Argentina represent more than 95% of all tropical glaciers globally, they are relatively sparsely studied in general, and particularly by using remote-sensing approaches. However, studies from the 1930s used terrestrial imaging, and aerial photographs are available from the 1950s on. In this article, we review the literature on remote sensing of the glaciers in the tropical Andes, divided into the four climatic sub-regions: inner tropics, dry outer tropics, northern wet outer tropics, and southern wet outer tropics. The majority of studies used optical remote sensing, particularly Landsat and Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) imagery, although shadows produced by steep terrain and often dense cloud cover – within the Intertropical Convergence Zone (ITCZ) of the inner tropics – are challenges to data analyses. Microwave and lidar remote sensing have been successfully employed in some studies. The vast majority of glacier monitoring studies documented glacier recessions throughout the tropical Andes since the 1950s; most results are available for the Peruvian Andes, particularly the Cordillera Balance. Recent field tests explored the use of unmanned aerial systems (UAS) and lidar in glacier research; preliminary results are promising and have the potential to lead into new research directions.